Reproductive factors and cognitive impairment in natural menopausal women: A cross-sectional study - Xi, Haitao; Gan, Jinghuan; Liu, Shuai; Wang, Fei; Chen, Zhichao; Wang, Xiao-Dan; Shi, Zhihong; Ji, Yong (Frontiers in Endocrinology, 2022)
Introduction Little information on rural older women in northern China has been reported, apart from three studies in southern and eastern China in the past decade. This study aims to evaluate the relationships between reproductive factors and the risk of cognitive impairment, including mild cognitive impairment (MCI) and dementia, in Chinese women with natural menopause. Methods The cross-sectional study was conducted in 112 community primary healthcare centers in rural northern China between April 2019 and January 2020. A total of 4,275 women aged ≥65 years who had natural menopause were included. Reproductive factors as well as the reproductive period (= age at menopause − age at menarche) were recorded. The relationships between reproductive factors and cognitive impairment were evaluated by correlation and logistic regression analysis. Results Overall, 28.6% and 11.4% of women were diagnosed with MCI or dementia, respectively. In natural menopause women, the age at menopause (adjusted r = 0.070, p < 0.001), reproductive period (adjusted r = 0.053, p = 0.001), and number of pregnancies (adjusted r = −0.042, p = 0.007) and parities (adjusted r = −0.068, p < 0.001) were correlated with Mini-Mental State Examination (Chinese version) scores, and with similar findings concerning MCI and dementia with Lewy bodies (DLB). Greater age at menopause and a long reproductive period significantly decreased the risk of MCI and Alzheimer’s disease (AD), and more parities significantly increased the risks of MCI (odds ratio (OR) = 1.111, 95% confidence interval (CI): 1.039–1.187, p = 0.002), dementia (OR = 1.162, 95% CI: 1.061–1.271, p = 0.001), particular AD (OR = 1.131, 95% CI: 1.010–1.266, p = 0.032), DLB (OR = 1.238, 95% CI: 1.003–1.528, p = 0.047), and vascular dementia (VaD) (OR = 1.288, 95% CI: 1.080–1.536, p = 0.005). Conclusions The prevalence rates of MCI and dementia were 28.6% and 11.4% in older women. Greater age at menarche, young age at menopause, shorter reproductive period, and larger numbers of pregnancies/parities were correlated with poor cognition and significantly increased the risks of MCI and dementia, particularly AD, DLB, and VaD.